New Insights into How Trafficking Regulates T Cell Receptor Signaling - Lou, Jieqiong; Rossy, Jérémie; Deng, Qiji; Pageon, Sophie V.; Gaus, Katharina (Frontiers in Cell and Developmental Biology, 2016)
Abstract There is emerging evidence that exocytosis plays an important role in regulating T cell receptor (TCR) signaling. The trafficking molecules involved in lytic granule (LG) secretion in cytotoxic T lymphocytes (CTL) have been well studied due to the immune disorder known as familial hemophagocytic lymphohisiocytosis (FHLH). However, the knowledge of trafficking machineries regulating the exocytosis of receptors and signaling molecules remains quite limited. In this review, we summarize the reported trafficking molecules involved in the transport of the TCR and downstream signaling molecules to the cell surface. By combining this information with the known knowledge of LG exocytosis and general exocytic trafficking machinery, we attempt to draw a more complete picture of how the TCR signaling network and exocytic trafficking matrix are interconnected to facilitate T cell activation. This also highlights how membrane compartmentalization facilitates the spatiotemporal organization of cellular responses that are essential for immune functions.